A low‐frequency haplotype spanning SLX4/FANCP constitutes a new risk locus for early‐onset breast cancer (<60 years) and is associated with reduced DNA repair capacity. Issue 4 (30th October 2017) - Surowy, Harald; Varga, Dominic; Burwinkel, Barbara; Marmé, Frederik; Sohn, Christof; Luedeke, Manuel; Rinckleb, Antje; Maier, Christiane; Deissler, Helmut; Volcic, Meta; Wiesmüller, Lisa; Hasenburg, Annette; et al.
Abstract : Only a fraction of breast cancer (BC) cases can be yet explained by mutations in genes or genomic variants discovered in linkage, genome‐wide association and sequencing studies. The known genes entailing medium or high risk for BC are strongly enriched for a function in DNA double strand repair. Thus, aiming at identifying low frequency variants conferring an intermediate risk, we here investigated 17 variants (MAF: 0.01–0.1) in 10 candidate genes involved in DNA repair or cell cycle control. In an exploration cohort of 437 cases and 1189 controls, we show the variant rs3810813 in the SLX4/FANCP gene to be significantly associated with both BC (≤60 years; OR = 2.6(1.6–3.9), p = 1.6E‐05) and decreased DNA repair capacity (≤60 years; beta = 37.8(17.9–57.8), p = 5.3E‐4). BC association was confirmed in a verification cohort ( N = 2441). Both associations were absent from cases diagnosed >60 years and stronger the earlier the diagnosis. By imputation we show that rs3810813 tags a haplotype with 5 additional variants with the same allele frequency ( R 2 > 0.9), and a pattern of association very similar for both phenotypes (cases <60 years, p < 0.001, the Bonferroni threshold derived from unlinked variants in the region). In young cases (≤60 years) carrying the risk haplotype, micronucleus test results are predictive for BC (AUC > 0.9). Our findings propose a risk variant with high penetrance on the haplotype spanning SLX4/FANCP to be functionally associated to BC predisposition via decreased repair capacity and suggest this variant is carried by a fraction of these haplotypes that is enriched in early onset BC cases. Abstract : What's new? While genome‐wide associations studies (GWASs) have successfully identified susceptibility genes in breast cancer, they have largely missed rare and low‐frequency alleles. Here, using a candidate gene approach focused on low‐frequency alleles, a new susceptibility locus was discovered for early‐onset breast cancer. The haplotype carrying the causal variant spanned the SLX4 / FANCP gene and was associated with reduced DNA repair capacity. Because the variant was absent in patients over age 60, the association could not be detected by GWAS without age stratification. The findings suggest that the low‐frequency variant is highly penetrant and may carry significant risk for early‐onset breast cancer.